Assessing the quality, efficiency and usefulness of the Western Australian population-based Intellectual Disability Exploring Answers (IDEA) surveillance system: a surveillance system evaluation. Issue 10 (18th October 2019) - Strobel, Natalie A; Bourke, Jenny; Leonard, Helen; Richardson, Alice; Edmond, Karen M; McAullay, Daniel
Abstract : Objectives: Our overall aim was to evaluate the Western Australian Intellectual Disability Exploring Answers (IDEA) surveillance system. The primary objective was to evaluate the attributes of the system. The secondary objective was to provide recommendations to data custodians and stakeholders to strengthen the system. Method: The IDEA system was evaluated using process observation, interviews and secondary data analysis of system attributes: usefulness, simplicity, data quality, acceptability, representativeness, timeliness and stability. 2001 US Centers for Disease Control and Prevention guidelines were used. Results: We found that the IDEA system was useful, simple, flexible, acceptable, representative, timely and stable. We compared individuals from the IDEA system (n=10 593) with those with cerebral palsy and intellectual disability (ID) (n=582) from another surveillance system. Of the 582 with cerebral palsy and ID, 501 (86.1%) were in the IDEA system and 81 (13.9%) were not. In total, 0.7% of cases (81/10674) with ID were not identified in the IDEA system. There were little differences in cases that were not identified in the IDEA system between Indigenous status, sex and place of residence. Conclusions: The strengths of the IDEA system include having a high data quality resource contributing to national and international data on ID, strong government support and a dedicated management team. Output from studies linking to IDEA data have had major contributions to the international literature about ID. However, limited resources have prevented it from realising its full potential in relation to translational activities. The IDEA system is a valuable resource to address the needs of people living with ID.